ANALISIS PENGARUH PENGEMBANGAN EKSTRAKULIKULER PRAMUKA TERHADAP KEDISIPLINAN SISWA DI SMP JAYA BAKTI JAKARTA - Daman Rasman Syarif Hidayat (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2019)
Efforts to develop national character through various learning activities and living habits, like religious, honest, disciplined, tolerant, hard work, peaceful and peaceful, and responsible, are undertaken in schools. The common practice is to teach the proper and wrong knowledge and feel if the value is good or not. This study is a quantitative description of qualitative research. This research kind is a correspondence. All the kids who participated in Jaya Bakti Junior High School Jakarta's Scouting Extrascientific activities comprised 24 pupils. Total sampling methods were used to collect a sample of 24 students. The research sample the methodology for collecting data is a survey. Pearson's product-moment correlation with the help of the PLC program was employed in data analysis methodology. The association between SMP Jaya Bakti Jakarta Scouting and Student Discipline with a significance (0.000 < 0.05) is positive and significant, this study demonstrates. Student discipline must be taken into account, as discipline is an initial key for the formation of students. Scouting discipline has a major influence on kids' molding.